Antenatal Care (ANC) in Pregnant Women with Preeclampsia in Agroindustrial Jember, Indonesia - Rahmawati, Iis; Septiyono, Eka Afdi; Kurniawati, Dini (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the presence of antenatal care in pregnant women with preeclampsia in agroindustrial Jember, Indonesia. Study Design: Cross-sectional study. Place and Duration of Study: Banjarsengon, Panti, and Tempurejo Health Centers, Jember, Eats Java, Indonesia from Sep 2022 to Jan 2023. Methodology: A total of 240 women, diagnosed with preeclampsia, comprised the sample for this study which was enrolled employing a purposive sampling technique. All participants were pregnant women at risk of preeclampsia, those currently experiencing preeclampsia, and postpartum women who had encountered preeclampsia. Data was collected through the usage of the Quality of Prenatal Care Questionnaire (QPCQ), which includes 6 subscales and 46 statement items. Result: ANC service quality in the Banjarsengon, Panti, and Tempurejo Health Centers in Jember Regency, with regard to support and respect subscale, was found to be the highest average value (Mean±SD, CI; 4.18±0.31, 3.58 - 5.00) however, the approachability subscale exhibited the lowest average value (Mean±SD, CI; 2.36±0.48, 1.25 - 4.00). Conclusion: Pregnant women with preeclampsia need assistance, monitoring, and referral by health workers. Health workers providing antenatal care services must prioritize support and respect so that pregnant women